2020
DOI: 10.7759/cureus.11628
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Need for Abdominal CT Scan in Trauma Patients With a Low-Risk Mechanism of Injury and Normal Vital Signs?

Abstract: Background Clinically significant injuries are often missed in trauma patients with low-risk mechanisms of injury and lack of "red flags," such as abnormal vital signs. The purpose of this retrospective analysis was to evaluate the efficacy of computed axial tomography (CT) for identifying occult injuries in a high-volume trauma center. Methods Records from our institutional trauma registry were retrospectively extracted, examining encounters from January 2015 to October 2019. Those patients between the ages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…It will delay the dealing with the missed injury and likely to prolong the hospitalization and increase morbidity and mortality. 5,6 Like our study, other study found longer hospitalization period in missed injury group, 7 if we do not include the initial hospitalization period, it was not found significant in this study, as we took decision within 24-28 hrs. Hospitalization cost is also an important factor in therapy, but the whole period was treated free in military hospital, hence it was not taken into consideration.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…It will delay the dealing with the missed injury and likely to prolong the hospitalization and increase morbidity and mortality. 5,6 Like our study, other study found longer hospitalization period in missed injury group, 7 if we do not include the initial hospitalization period, it was not found significant in this study, as we took decision within 24-28 hrs. Hospitalization cost is also an important factor in therapy, but the whole period was treated free in military hospital, hence it was not taken into consideration.…”
Section: Discussioncontrasting
confidence: 45%
“…4 In such scenario, high resolution CT screening is recommended. 5 In abdominal trauma, the findings of CT are based on the amount of bleeding. More is the intra-abdominal bleeding more is the CT scan findings.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous contrast-enhanced CT scans are now the standard for diagnosing splenic injuries, with The EAST Practice and Management Guideline noting that CT scans are the most accurate, specific, and sensitive in identifying and characterizing splenic injury [15] , [16] . CT scans often diagnose occult injuries and injuries that would have been missed if based on clinical examination solely; yet, the literature also suggests that the rate of missed splenic vascular injuries remains largely unknown [14] , [17] , [18] . Moreover, it is possible that index imaging may be inadequate and fail to capture vascular damage or parenchymal disruption, especially due to contrast timing or patient motion [13] .…”
Section: Discussionmentioning
confidence: 99%
“…For treatment in our patient, a splenectomy was ultimately completed to handle the DSR. Management of splenic injuries with NOM has become increasingly popular, even in more severely injured spleens [18] . NOM has had escalating success over the years, especially with the incorporation of splenic angioembolization as an adjunct [19] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients, particularly infants and young children, are more sensitive to radiation exposure compared to adults. Their increased radiosensitivity stems from their developing bodies, higher metabolic rates, and longer life expectancies, which provide more time for potential radiation-related effects to manifest [ 6 , 25 , 50 ]. Therefore, guidelines for pediatric CT imaging generally aim to minimize unnecessary radiation exposure [ 51 ].…”
Section: Discussionmentioning
confidence: 99%